The devil may dance : a novel - Tapper, Jake (Little, Brown and Company, 2021)
In a fast-paced sequel to The Hellfire Club, Charlie and Margaret Marder, political stars in 1960s Washington D.C., arrive in Los Angeles on their latest case, only to be pursued by sinister forces from Hollywood's stages to the newly founded Church of Scientology.